2007
DOI: 10.1111/j.1744-313x.2007.00709.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of TLR2 gene Arg753Gln polymorphism with urinary tract infection in children

Abstract: The aim of this study is to investigate Arg753Gln allele polymorphisms of toll-like receptor-2 (TLR2) gene distribution, allele frequency in urinary tract infection (UTI) and genotype-phenotype association of TLR2 gene in children with UTI. The polymorphism was investigated in 124 children with UTI (22 boys and 102 girls; mean age 5.81 +/- 3.47 years) with direct DNA sequencing-based method. TLR2 gene Arg753Gln allele frequency was higher in the patient group when compared with control group (OR 3.14, 95%CI 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
62
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 31 publications
1
62
1
1
Order By: Relevance
“…Clinical studies showed that only a fraction of r-UTI patients had obvious functional, anatomic and behavioral risk factors, which were considered to be strongly associated with an increased risk of r-UTI. Recently, genetic studies have reported the associations of polymorphisms within innate immune molecules such as Toll-like receptor 2 and 4 (TLR2 and TLR4) with r-UTI susceptibility (Karoly et al 2007;Lundstedt et al 2007;Tabel et al 2007;Hawn et al 2009). The host genetic factor has been considered as one of the pathogenesis of r-UTI.…”
mentioning
confidence: 99%
“…Clinical studies showed that only a fraction of r-UTI patients had obvious functional, anatomic and behavioral risk factors, which were considered to be strongly associated with an increased risk of r-UTI. Recently, genetic studies have reported the associations of polymorphisms within innate immune molecules such as Toll-like receptor 2 and 4 (TLR2 and TLR4) with r-UTI susceptibility (Karoly et al 2007;Lundstedt et al 2007;Tabel et al 2007;Hawn et al 2009). The host genetic factor has been considered as one of the pathogenesis of r-UTI.…”
mentioning
confidence: 99%
“…These findings have been taken as indicative of a genetic determinant in the susceptibility to recurrent UTI. The immunological status of UTI-prone women has not previously been well characterized, but there is some indication that genetic polymorphism related to induction of immune responses could contribute to the susceptibility (15,45). Cell-mediated innate responses (in particular, neutrophil action) form the basis of the defense against genitourinary tract infections (44).…”
mentioning
confidence: 99%
“…Polymorphism in several genes (Interleukin -1B [IL -1B], Tumor Necrosis Factor -α [TNF -α ], TLR -2, TLR -4, etc.) may infl uence the predisposition to BV, VVC, UTI, and risk for preterm deliveries in different ethnic groups (e.g., Caucasian, black, and Brazilian women; Cauci et al 2007 ;Genc et al 2007 ;Giraldo et al 2007 ;Karoly et al 2007 ;Tabel et al 2007 ). These examples indicate the complexity of the microbial -host interactions, in which the relationships established between the probiotic bacteria and the host immune system are included.…”
Section: Immune System At the Ugtmentioning
confidence: 99%